2017
DOI: 10.1016/j.mulfin.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical co-movements of private real estate, public real estate and equity markets: A cross-continental spectrum

Abstract: Whether returns from investing in real estate shares reflect equity market or real estate market trends is an important question for investors seeking liquid, low cost exposure to real estate. We consider the relationship between real estate shares, private real estate investments and equity markets for five locations: Australia, Hong Kong, Singapore, UK and US. We utilise spectral and cross-spectral techniques to decompose each time series into cyclical components of differing frequencies. This allows correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Another very interesting aspect of research, indirectly dealing with cyclicality, is associated with the problem of the effectiveness of stimulating it through government interventions (Zhou, 2018) and the presentation of how uncertainty of economic policy affects the housing market (Huang et al, 2018). Discussion concerned with the identification of periodic components, including cyclical component in the time series characterizing the construction market, in particular the housing market are explored in other studies (Bengtsson et al, 2018;Devaney and Xiao, 2017;Fan et al, 2019;Gabauer and Gupta, 2020;Liow and Newell, 2016;Yépez, 2018). As we mentioned above, the ability to determine the phase of the cycle of construction market is of particular assistance in determining the development potential of this market.…”
Section: Construction Market -Analysis Of Effects On the Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Another very interesting aspect of research, indirectly dealing with cyclicality, is associated with the problem of the effectiveness of stimulating it through government interventions (Zhou, 2018) and the presentation of how uncertainty of economic policy affects the housing market (Huang et al, 2018). Discussion concerned with the identification of periodic components, including cyclical component in the time series characterizing the construction market, in particular the housing market are explored in other studies (Bengtsson et al, 2018;Devaney and Xiao, 2017;Fan et al, 2019;Gabauer and Gupta, 2020;Liow and Newell, 2016;Yépez, 2018). As we mentioned above, the ability to determine the phase of the cycle of construction market is of particular assistance in determining the development potential of this market.…”
Section: Construction Market -Analysis Of Effects On the Economymentioning
confidence: 99%
“…Other studies concerned with the broadly understood investing in the housing market investigate the viability of investing in various investment options, and explores whether returns on investment in the shares of housing companies follow trends in the stock market. Another study examined the relationship between real estate stocks and private real estate investments (Devaney and Xiao, 2017). The next important research issue was associated with the exploration of the possibilities of diversifying investment portfolios through real estate investment funds (REIT) (La and Mei, 2015;Piao et al, 2016).…”
Section: Construction Market -Analysis Of Effects On the Economymentioning
confidence: 99%
“…Several other studies have found this relationship to be weak, such as Barkham and Gelnter (1995), Mueller and Mueller (2003) and Hoesli and Moreno (2007). Hoesli and Oikarinen (2012) and Devaney and Xia (2017) find Australian market evidence of no significant co-movement for these assets, however these findings use appraisal-based returns, which can distort findings (see below).…”
Section: Introductionmentioning
confidence: 86%
“…This also proves to better align REITs and real estate but has only been applied to the US market. Furthermore, many studies use appraisal-based direct returns given data availability, such as in the studies by Hoesli and Oikarinen (2012) and Devaney and Xia (2017) for Australian returns. However, these returns suffer from smoothing bias, which reduces volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies analysed the justification of investing in various options while considering whether returns on investment in real estate stock reflect trends on the stock market. The relations between real estate stock were examined in correlation with private real estate investments (Devaney and Xiao, 2017). A presentation of the opportunities for diversifying the investment portfolio through investment funds in real estate was the next important research topic (REIT) (La and Mei, 2015;Piao, Mei, and Xue, 2016).…”
Section: A Literature Review On the Time-frequency Analysis Within Thmentioning
confidence: 99%